Editorial Volume 4, Issue 1 - Ciorstan J. Smark (Australasian Accounting, Business and Finance Journal, 2010)
This journal was started with the generous support and encouragement of the School of Accounting and Finance at the University of Wollongong. From its inception, the journal has invited and had submissions of manuscripts from senior staff within the school, the distinguished diasporas of former colleagues and visiting scholars; and the larger academic community of which the School has had a long history of engagement. Notably, Michael Gaffikin (2007), Warwick Funnell (2007), Mary Kaidonis (2008), Ed Arrington (2007) and Alex Frino (Tan, Frino, and Jarnecic, 2007) all contributed manuscripts to the fledgling first issues.